RNA sequencing of single allergen‐specific memory B cells after grass pollen immunotherapy: Two unique cell fates and CD29 as a biomarker for treatment effect. Issue 3 (1st October 2022) - McKenzie, Craig I.; Varese, Nirupama; Aui, Pei Mun; Reinwald, Simone; Wines, Bruce D.; Hogarth, P. Mark; Thien, Francis; Hew, Mark; Rolland, Jennifer M.; O'Hehir, Robyn E.; van Zelm, Menno C.
Abstract: Background: Sublingual immunotherapy (SLIT) for grass pollen allergy can modify the natural history of allergic rhinitis and is associated with increased allergen‐specific IgG4 . IgG4 competitively inhibits functional IgE on the surface of effector cells, such as mast cells and basophils, from binding to allergens. To further understand the important role memory B‐cell (Bmem) responses play in mediating the beneficial effects of SLIT, we assessed changes in allergen‐specific Bmem subsets induced by SLIT for grass pollen allergy. Methods: Blood samples were collected twice outside the pollen season from twenty‐seven patients with sensitization to ryegrass pollen (RGP; Lolium perenne ) and seasonal rhinoconjunctivitis. Thirteen received 4‐month pre‐seasonal SLIT for grass pollen allergy, and 14 received standard pharmacotherapy only. Single‐cell RNA sequencing was performed on FACS‐purified Lol p 1‐specific Bmem before and after SLIT from four patients, and significant genes were validated by flow cytometry on the total cohort. Results: Four months of SLIT increased RGP‐specific IgE and IgG4 in serum and induced two Lol p 1‐specific Bmem subsets with unique transcriptional profiles. Both subsets had upregulated expression of beta 1 integrin ITGB1 (CD29), whereas IGHE (IgE), IGHG4 (IgG4 ), FCER2 (CD23), and IL13RA1 were upregulated in one subset. There was an increase in the proportion of Lol p 1 + Bmem expressing surface IgG4, CD23, and CD29 after SLIT. Conclusions: A clinically successful 4 months course of SLIT for grass pollen allergy induces two transcriptionally unique Bmem fates. Associated changes in surface‐expressed proteins on these Bmem subsets can be used as early biomarkers for treatment effects. Abstract : Using recombinant Lol p 1 tetramers, allergen‐specific Bmem from patients allergic to ryegrass pollen were examined before and after 4 months of SLIT. Single‐cell RNA sequencing revealed that SLIT drives two unique transcriptional Bmem fates, typified by CD23, IgG4, IgE, CD29, and IL13Ra1 expression. Flow cytometry confirmation revealed that CD29 expression is the best positive predictor of SLIT effects.Abbreviations: AR, allergic rhinitis; Bmem, memory B cells; FCER2, Fc epsilon receptor II; IGH, immunoglobulin heavy chain; IL13RA1, interleukin 13 receptor subunit alpha 1; ITGB1, integrin subunit beta 1; SLIT, sublingual immunotherapy.